Multiyear sea ice export through the Bering Strait during winter 2011–2012. Issue 10 (16th October 2013) - Babb, David G.; Galley, Ryan J.; Asplin, Matthew G.; Lukovich, Jennifer V.; Barber, David G.
Abstract : [1] Six ice beacons deployed in the Beaufort Sea during August 2011 tracked the anomalous export of multiyear sea ice from the Chukchi Sea through the Bering Strait to the Bering Sea between November 2011 and May 2012. These are the first observations in 34 years of ice beacon export through the Bering Strait. Using 34 years of passive microwave derived ice motion fields, we find that during 2011–2012 southward ice motion in the Chukchi Sea persisted for a record six of seven months and that sea ice speeds were significantly faster than the long term mean. The combination of increased ice speeds and reduced likelihood of ice arch development through the strait culminated in the record export of 13.5 × 10 3 km 2 of sea ice through the Bering Strait. Monthly sea level pressure fields, dominated by an Aleutian Low and Siberian High, show anomalies in December and January played a role in initiating this event and forced multiyear ice into the southern Chukchi Sea. However, these variations were small and typical of this area, yet we find no evidence of a similar export event in the last 34 years even though the forcing was similar to the climatology. This leads us to attribute this event to a change in the responsiveness of the Arctic ice pack to typical forcing mechanisms. Key Points: Multiyear sea ice was exported through the Bering Strait during winter 2011–2012 In 2011–2012 the Bering Strait exported 3x the maximum ice export from 1979–2012 Sea ice has become increasingly mobile across the Bering Strait in recent years